Cross section measurement of 241Am(n,f) reaction at the Experimental Area 2 of the n_TOF facility at CERN: First Results - Eleme, Zinovia; et al., ... (HNPS Advances in Nuclear Physics, 2020)
The condition for the safe design and operation of fast neutron reactors and energy boosters (Generation-IV reactors, ADS systems [1]) is the accuracy of nuclear data. The 241Am isotope (T1/2 = 433 years) is highly present in nuclear waste, accounting for about 1.8% of the actinide mass in PWR UOx nuclear reactors’ waste [2]. In addition, the 241Am isotope is further produced by the β decay of the 241Pu isotope (T1/2 = 14.3 years). Given the high production rate of 241Am isotope, its incineration with concurrent energy production is considered to be of utmost importance for the design and implementation of the recycling of existing nuclear waste. Sensitivity studies of the proposed systems for energy production showed that high-precision measurements of the cross section of the 241Am(n,f) reaction are required. In the present work, the 241Am(n,f) reaction cross section was measured in the Second Experimental Area of the n_TOF facility at CERN, using an array of Micromegas detectors. For the measurement, six targets of 241Am with average activity of 17 MBq per sample were coupled with an equal number of detectors in a common chamber. Additionally two 235U and two 238U samples were coupled with Micromegas detectors utilizing the neutron flux determination. Within this work, an overview of the experimental set-up and the adopted data analysis technique is presented along with preliminary results.